2012
DOI: 10.1016/j.ajpath.2012.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Mutations of the Serine Protease CAP1/Prss8 Lead to Reduced Embryonic Viability, Skin Defects, and Decreased ENaC Activity

Abstract: CAP1/Prss8 is a membrane-bound serine protease involved in the regulation of several different effectors, such as the epithelial sodium channel ENaC, the protease-activated receptor PAR2, the tight junction proteins, and the profilaggrin polypeptide. Recently, the V170D and the G54-P57 deletion mutations within the CAP1/Prss8 gene, identified in mouse frizzy (fr) and rat hairless (fr(CR)) animals, respectively, have been proposed to be responsible for their skin phenotypes. In the present study, we analyzed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(62 citation statements)
references
References 47 publications
2
58
2
Order By: Relevance
“…2 Of high clinical relevance, both transient and late treatment with ICG-001 restored podocyte function and repressed proteinuria, renal inflammation, and fibrosis. The latter is consistent with the findings of many studies that documented potent antifibrotic effects of canonical Wnt signaling blockade in the kidney, 4 lung, 5 skin, 6 and other organs. It also provides an exciting link between the RAS, TGF-b, and the Wnt/b-catenin pathway.…”
Section: Disclosuressupporting
confidence: 79%
See 2 more Smart Citations
“…2 Of high clinical relevance, both transient and late treatment with ICG-001 restored podocyte function and repressed proteinuria, renal inflammation, and fibrosis. The latter is consistent with the findings of many studies that documented potent antifibrotic effects of canonical Wnt signaling blockade in the kidney, 4 lung, 5 skin, 6 and other organs. It also provides an exciting link between the RAS, TGF-b, and the Wnt/b-catenin pathway.…”
Section: Disclosuressupporting
confidence: 79%
“…7 Recent data also demonstrate that TGF-b stimulates canonical Wnt signaling by decreasing the expression of the Wnt antagonist Dickkopf-1, highlighting how both pathways interact to mediate fibrotic diseases. 6 Together with TGF-b1, b-catenin also contributes to the epithelial cell phenotype switch known as…”
Section: Disclosuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have emphasized the importance of CAP1/Prss8 in vivo [32][33][34][35] and its implication in ENaC regulation in alveolar fluid clearance and lung fluid balance. 26 In colon, we clearly identify CAP1/Prss8 as a protease activating ENaC in vivo, because on RS and LS diets, ENaC-mediated transport becomes limiting in Prss8 KO mice (Figure 7).…”
Section: Cap1 Regulates Colon Enac Activity By Blunting Its Circadianmentioning
confidence: 99%
“…Detailed phenotypic analysis revealed that the matriptase/prostasin pathway is essential for terminal epidermal differentiation as well as tight junction formation and, as a result, the loss of matriptase or prostasin function leads to a severe defect in epidermal barrier function, and an abnormal hair follicle maturation (Leyvraz et al, 2005;List et al, 2009List et al, , 2003. Subsequent studies using tissue-specific knockout mice to bypass the postnatal lethality revealed that matriptase and/or prostasin play crucial roles in epithelial development and function in a wide variety of mouse tissues including placenta, skin, salivary gland, intestines, lungs and thymus (Frateschi et al, 2012;List et al, 2009;Malsure et al, 2014;Planes et al, 2010;Szabo et al, 2014).…”
Section: Introductionmentioning
confidence: 99%